New non-pharmaceutical methods for the treatment of resistant arterial hypertension - A. V. Rodionov; I. E. Shumilova; V. I. Makolkin (Кардиоваскулярная терапия и профилактика)
The review presents new non-pharmaceutical methods for the treatment of resistant arterial hypertension, such as carotid sinus stimulation and renal sympathetic denervation. The authors analyze the results of the clinical studies on efficacy and safety of these new methods.